PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESIBILITASNYA TERHADAP TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH DI PEMERINTAHAN KABUPATEN KEPULAUAN TALAUD - Poae, Dedy Aries; Saerang, David P. E (ACCOUNTABILITY, 2013)
At the time of onset of regional autonomy in the hope that emerges is more independent local governments in the implementation of government activities and conduct development in their respective areas. Government Regulation Number 24 of 2005 Government Accounting Standards neighbor besides achieving good governance is also the answer to anticipation the financial reporting guidelines that can be generally accepted.The research was conducted at the head and the staff involved in the process of financial management in the Government District Talaud Islands. This study aimed to determine the effect of financial statement presentation and accessibility to transparency and accountability in government financial management goverment Talaud Islands.Data analysis method used is the method of multiple linear regression, descriptive statistics test, test validity and reliability testing, test assumptions of classical, hypothesis testing  ( F test and t test ) , the coefficient of determination  ( R ² ) . To complete the overall data analysis used SPSS 20.0 software.The results show the financial statement presentation and accessibility significantly affect the transparency and accountability of financial management. It can be seen from the equation Y = 5,425 + + 0.579X1 0.094X2. Of multiple linear regression equation shows that the financial statement presentation and accessibility positive effect on transparency and accountability in the management of the financial statements. The correlation coefficient  ( R )  obtained for 65.3% and the coeffi cient of determination  ( R ² )  of 42.7% and the remaining 57.3% or other variables not examined in this study. Results of hypothesis testing  ( F test )  showed a significance value of 0.000 at the significant level α = 0.05 level test results mean F states H0 rejected Ha accepted. And  ( t test )  showed for the variable X1  ( Regions Financial Statements )  significant value for 0000 with a significant level of α = 0.05 then H0 is rejected means-Ha is accepted, it means the area of financial statement presentation variables significantly affect the transparency and accountability of financial management. For the variable X2  ( Aksesibilitan Regional Financial Statements )  significant value of 0.526 with a significant level of α = 0.05 then H0 is accepted means Ha rejected, meaning that the variable with Regional Financial Statements do not significantly affect the Transparency and Accountability of Financial Management.